Mutation analysis of NPHP6/CEP290 in patients with Joubert syndrome and Senior–Løken syndrome. Issue 10 (6th July 2007) - Helou, Juliana; Otto, Edgar A; Attanasio, Massimo; Allen, Susan J; Parisi, Melissa A; Glass, Ian; Utsch, Boris; Hashmi, Seema; Fazzi, Elisa; Omran, Heymut; O'Toole, John F; Sayer, John A; et al.
Abstract : Background: Nephronophthisis (NPHP) is an autosomal recessive cystic kidney disease that constitutes the most common genetic cause of renal failure in the first three decades of life. Using positional cloning, six genes ( NPHP1 - 6 ) have been identified as mutated in NPHP. In Joubert syndrome (JBTS), NPHP may be associated with cerebellar vermis aplasia/hypoplasia, retinal degeneration and mental retardation. In Senior–Løken syndrome (SLSN), NPHP is associated with retinal degeneration. Recently, mutations in NPHP6/CEP290 were identified as a new cause of JBTS. Methods: Mutational analysis was performed on a worldwide cohort of 75 families with SLSN, 99 families with JBTS and 21 families with isolated nephronophthisis. Results: Six novel and six known truncating mutations, one known missense mutation and one novel 3 bp pair in-frame deletion were identified in a total of seven families with JBTS, two families with SLSN and one family with isolated NPHP.